(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2023)
The lack of rapid diagnosis of tuberculosis with pathogen resistance to isoniazid with preserved sensitivity to rifampicin (IR-TB) may be the reason for low effectiveness of therapy and lead to amplification of drug resistance, including the formation of multidrug resistance. The aim of the work was to determine the incidence of IR-TB in the modern population, to characterize the phenotypic sensitivity and genetic determinants of resistance to isoniazid in representatives of this group of M. tuberculosis using representative material. We analyzed the results of drug susceptibility testing obtained from the study of M. tuberculosis isolates / M. tuberculosis DNA isolated from patients with pulmonary tuberculosis from the clinical departments of the Central Research Institute of Tuberculosis using molecular genetic and/or cultural methods for the period 2020–2023. The incidence of IR-TB was 10% of all detected cases of tuberculosis. M. tuberculosis with IR were both monoresistant to isoniazid (40%) and multiresistant (resistant to 3–5 antituberculosis drugs), and resistance to isoniazid was caused by mutations in the katG gene, leading to a high level of resistance.Based on an analysis of literature data and our own observations, the importance of the development and implementation of new simple molecular tests to determine resistance to both rifampicin and isoniazid is emphasized.